Effect of a Mid-Rotation Clerkship Director Meeting on Student Perception of the Obstetrics and Gynecology Clerkship. (October 2015) - Valentine, Meghan L.; Sonn, Tammy; Dukes, Jonathan
Abstract : STUDY OBJECTIVE: To examine the effect of a mid-rotation clerkship director feedback meeting on medical student perception of the obstetrics and gynecology clerkship educational experience. METHODS: This is a retrospective cohort study of third-year medical students completing a 6-week obstetrics and gynecology clerkship. The intervention was a 20-minute mid-rotation clerkship director feedback session during week 4 of the obstetrics and gynecology clerkship. The topics discussed during these meetings included performance to date based on resident feedback, progress of patient or procedure log card completion, and the student's general assessment of teaching on the clerkship. RESULTS: A mid-rotation clerkship director feedback session was implemented in July of 2012 at Washington University. We examined third-year medical student's clerkship evaluations from the 2011 to 2012 academic year (n=109), immediately before the implementation of the mid-rotation feedback session, to the 2012–2013 academic year (n=107). Evaluations were based on a 5-point Likert scale, which were compared using Student t test. The question pertaining to the quality of the educational experience improved, from a mean of 3.5–4.2, P <.0001. CONCLUSION: A mid-rotation clerkship director feedback session improves overall quality of the clerkship.